Edukasi Kesehatan Reproduksi Terhadap Siswa/I Kelas 5 & 6 SDN 139 Inpres Benteng Sanrobone Kabupaten Takalar - Hadzmawaty Hamzah; Liliskarlina Liliskarlina; Nurul Wahidah Hasan (Universitas Patria Artha, 2025)
Reproductive health is an essential aspect of children’s growth, particularly during puberty. However, many elementary school students have limited knowledge about physical changes and the importance of maintaining reproductive hygiene. This community service activity aimed to improve the knowledge and awareness of students at SDN 139 Inpres Benteng Sanrobone regarding reproductive health through interactive education. The activity employed lectures, discussions, and question—answer sessions, supported by educational media such as the book “My First Puberty” and posters. The results indicated an increase in students’ understanding of puberty changes, personal hygiene, and healthy behaviors. Simple evaluation through oral questioning showed that more than half of the students answered correctly after the session. Teachers also gained insights on how to deliver reproductive health materials in an age-appropriate and engaging manner. The activity received positive responses from both students and teachers and is recommended to be implemented continuously in elementary schools.